2019
DOI: 10.1021/acs.jchemed.8b01008
|View full text |Cite
|
Sign up to set email alerts
|

Improving College Student Success in Organic Chemistry: Impact of an Online Preparatory Course

Abstract: This quantitative study examines the impact of a three-week online organic preparatory course for chemistry undergraduates that is designed to improve student performance in the subsequent organic chemistry course series (N = 1,289). Organic chemistry often serves as a gatekeeper for students pursuing careers in science, technology, engineering, or mathematics (STEM). Because many students are underprepared for the rigorous organic chemistry series, and consequently are at greater risk of failing it, an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Given that academic preparedness, rather than LM status, contributed to student performance in the initial course, we encourage educational administrators and university instructors to aim interventions and support systems at the first course in college gateway science courses sequences for LM students and others who may be less well prepared, such as first generation or low SES students. These may include short preparatory online courses with foci in the intersection of the science content and the challenges posed by scientific language prior to the first course [ 51 , 52 ] or nudging intervention to increase motivation, self-efficacy and self-regulatory abilities [ 37 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that academic preparedness, rather than LM status, contributed to student performance in the initial course, we encourage educational administrators and university instructors to aim interventions and support systems at the first course in college gateway science courses sequences for LM students and others who may be less well prepared, such as first generation or low SES students. These may include short preparatory online courses with foci in the intersection of the science content and the challenges posed by scientific language prior to the first course [ 51 , 52 ] or nudging intervention to increase motivation, self-efficacy and self-regulatory abilities [ 37 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such factors may include student-level factors such as self-regulatory skills, student motivation, and study skills [ 59 61 ]; instructor-level factors such as teaching quality, teaching experience, instructional styles, and choice of the textbook [ 5 , 19 , 62 ]; and context-level factors such as scheduling of the classes, department funding, and the perceived chilly climate often reported in STEM learning environments [ 27 , 63 , 64 ]. Another strand of research may develop and evaluate interventions attempting to narrow this initial gap in lecture course performance for LM students such as short preparatory courses [ 51 , 52 ]; or nudging interventions [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that expansion of online learning is an important goal of many institutions ( 45 ), particularly as a way to decrease costs ( 62 ), it is important to continue to explore the advantages and disadvantages of each ( 63 – 65 ). Online instruction can offer many advantages for students ( 66 , 67 ), providing students with greater access to courses, even from distant campuses, as well as greater scheduling flexibility. Indeed, many students in our survey indicated an increased interest in remote learning given their experience during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study is relevant to the current teaching modality during the pandemic. Although the study setting of incorporating hybrid course formats was pre-pandemic, the results indicated hybrid modalities may be as effective as in-person courses, which may help departments see value in online course offerings even after the pandemic (Bourne et al 2005 ; Fischer et al 2019 ; Lei and Gupta 2010 ). Future studies might further examine the role of project-based, hands-on introductory engineering courses and the development of self-efficacy, effort regulation and interest in engineering on more distal student success factors such as major persistence, retention, graduation rates, and time-to-degree.…”
Section: Discussionmentioning
confidence: 99%